The Role Of Pondok Pesantren In Learning Arabic Language Skills In Indonesia - Ahmad Miftahun Ni'am (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2023)
Pondok pesantren is an Islamic institution that teaches santri on religion, character, values of life, and always controling them for 24 hours. Pondok pesantren usually consist of kyai and as the leader and teacher, santri as people who seek knowledge, masjid as one of the centers of learning activities. Beside learning about Islamic religion the scolar also learning Arabic language because of many study sources using Arabic language. Teaching and learning activities in Islamic boarding schools almost entirely use Arabic both in their textbooks and their study. Therefore learning Arabic in Indonesia has grown in to learn Arabic language skills. Arabic learning activities at pondok pesantren usually consist of Bandongan, Sorogan, Muhadhoroh, Muhadastah, and Imla'. Although there are still deficiencies in some of these learning, it is not as a setback, but as an evaluation to develop Arabic language skills in Indonesia to be better development in the future.